Tuning the Network Structure in Poly(vinylidene fluoride)/Carbon Nanotube Nanocomposites Using Carbon Black: Toward Improvements of Conductivity and Piezoresistive Sensitivity - Ke, Kai; Poetschke, Petra; Wiegand, Niclas; Krause, Beate; Voit, Brigitte (ACS Applied Materials and Interfaces, 2016)
Piezoresistive poly(vinylidene fluoride) (PVDF) nanocomposites are very intriguing for strain sensor applications in structural health monitoring (SHM) systems. In general, high piezoresistive sensitivity combined with broad measurable strain ranges are greatly favored in those sensors. Here, a facile strategy, i.e. constructing strain susceptible conductive networks using hybrid filler systems consisting of carbon nanotubes (CNTs, 0.5-1 wt %) and carbon black (CB, 0.5-4 wt %), was introduced to tune both electrical conductivity and piezoresistive sensitivity of melt mixed PVDF nanocomposites. At the same filler content CNTs, due to their larger aspect ratio, contribute more to electrical conductivity improvements of nanocomposites than CB, while contacts between CB particles are more sensitive to tensile strain. With retained ductility of PVDF, tunable electrical conductivity and ΔR/R0-strain sensitivity can be achieved by combining the advantages of CNTs and CB by adjusting the conductive network structure. Conductivity improvement is more remarkable if the mass ratio of CNTs to CB (mCNTs/mCB), varied between 1:1 and 1:4, is higher in hybrid filler compositions. Lower mCNTs/mCB ratios result in higher ΔR/R0 values in PVDF nanocomposites whether they have the same content of total filler or similar/the same initial electrical resistivity. At 10% tensile strain, the highest ΔR/R0 of 0.65 was obtained for the nanocomposite filled with 0.5 wt % CNTs and 0.5 wt % CB, while that for the counterpart containing 1 wt % CNTs is 0.35 at the same strain. The concept of using hybrid fillers provides a low-cost and effective way to fabricate piezoresistive polymer nanocomposites toward SHM applications.
CRIS-Team Scopus Importer:2023-03-20
Keywords: carbon black (CB); carbon nanotubes (CNTs); conductive network; conductive polymer nanocomposites (CPNCs); piezoresistivity